Combined use of drugs inhibiting the renin–angiotensin system: prescribing patterns and risk of acute kidney injury in German nursing home residents - Dörks M (Dove Medical Press, 2018)
Michael Dörks,1 Stefan Herget-Rosenthal,2 Falk Hoffmann,1 Kathrin Jobski1 1Department of Health Services Research, Carl von Ossietzky University Oldenburg, Oldenburg, Germany; 2Department of Medicine, Rotes Kreuz Krankenhaus, Bremen, Germany Background/aims: In 2012, the European Medicines Agency reviewed the safety of dual renin–angiotensin system (RAS) blockade because of potentially increased risks for inter alia acute kidney injury (AKI). Since residents of nursing homes are particularly vulnerable to adverse drug outcomes, the aims of our study were to describe RAS-inhibiting drug use in German nursing home residents and examine the risk of AKI associated with dual RAS blockade.Methods: Based on claims data, a nested case-control study within a cohort of RAS-inhibiting drug users was conducted. Using conditional logistic regression, confounder-adjusted odds ratios (aORs) and 95% confidence intervals (CI) were obtained for the risk of AKI associated with dual RAS blockade. Subgroup analyses were performed in patients with diabetes or chronic kidney disease and both comorbidities.Results: Of all 127,227 nursing home residents, the study cohort included 64,567 (50.7%) who were treated with at least one RAS-inhibiting drug. More than three quarters of the study population were female (77.1%). Mean age was 86.0 ± 6.8 years. Most residents were treated with angiotensin-converting enzyme inhibitors (77.8%), followed by angiotensin II receptor blockers (21.6%) and aliskiren (0.2%). Annual prevalence of dual RAS blockade declined from 9.6 (95% CI 7.8–11.8) in 2010 to 4.7 (95% CI 4.0–5.4) per 1,000 users in 2014. In the overall cohort, AKI was not significantly associated with dual RAS blockade (aOR 1.99; 0.77–5.17). However, significantly increased aORs were observed when considering patients with diabetes (3.47; 1.27–9.47), chronic kidney disease (4.74; 1.24–18.13) or both (11.17; 2.65–47.15).Conclusions: Prescribing of drugs inhibiting the RAS is common in German nursing homes. Though the prevalence of dual RAS blockade declined, our study showed an increased risk of AKI in patients with diabetes and/or chronic kidney disease. Therefore, cautious use is warranted in these vulnerable patients. Keywords: dual RAS blockade, nested case-control study, long-term care